Possibility for development of organic livestock breeding in area of Golija mountain - Slavica Arsić; Nataša Kljaić; Mirjana Savić (Ekonomika Poljoprivrede (1979), 2010)
Given to the structure and characteristics of the terrain, which is reflected in the large areas of grassland and grassy meadows, the area within the park of nature "Golija", there are excellent conditions for development of agriculture and livestock breeding, and therefore the production of milk and milk products. Organic livestock enables sustainable development of human communities in the regions covered with the modes of protection of natural resources, while providing the proper exploitation of existing agricultural areas and preventing further degradation of natural meadows and pastures. The subventions granted by the state for organic production, caused the appearance of the frst manufacturers who choose to switch to this type of agricultural production.